Temperature dependence of copper, iron, nickel and chromium transfers into various black and green tea infusions - (:unkn) unknown (My University, 1998)
Transfer ratios of copper, iron, nickel and chromium from 10 blended, unblended, instant and green tea samples of Turkish or British origin into the infusions have been determined at different brewing temperatures (18, 40, 60 and 80°C). The transfer ratio of each metal into the infusion appeared to be dependent on both temperature and strength of infusions as well as the kind of tea. Ingested metal amounts were calculated and discussed.
Keywords: Black tea; Chromium; Copper; Green tea; Iron; Nickel; Tea infusions